An Existentialist Enquiry into the Impact of the Levirate Custom on the Contemporary Kenyan Society - Vitalis , Abong‘o Ngore (African Journal of Education,Science and Technology (AJEST), 2015)
The traditional Kenya Luo community, in which the existing levirate custom was born, was communalistic in nature. Traditional Luo society thus put more emphasis on the community than the individual person, more on solidarity than on the needs and aspirations of the individual, and more on the communion of persons than on their autonomy. In fact, the society was more important than the individual. The main aim of this study is to give a critical appraisal of the levirate custom among the Luo of Kenya. This paper specifically examines the impact of this custom on the Luo society in particular and extends the discussion to show how it has affected the Kenyan society at large. The study was a qualitative type of research which was both library and field based. It employed the critical-analytical, phenomenological and the speculative philosophical methods, thus the holistic approach. It also used the Socratic and historical methods to trace the historical development of the custom. The questionnaires and tape recording were some of the tools used in data collection. Tables were used in data analysis and presentation. One of the major findings of the study indicates that the Luo levirate custom is oppressive to the widow. It undermines her freedom of choice, growth and development. The custom perpetuates male dominance and female subordination. It exacerbates poverty and spurs the spread of HIV/AIDS pandemic. The findings add to the limited yet much needed data on widows. It is also useful to policy makers and the different agencies dealing with gender equity, human rights, development and HIV/AIDS pandemic in the contemporary society.